Primary and secondary cardiovascular disease prevention interventions targeting lifestyle risk factors in women: A systematic review and meta-analysis - Slater, Kaylee; Colyvas, Kim; Taylor, Rachael; Collins, Clare E.; Hutchesson, Melinda (Frontiers in Cardiovascular Medicine, 2022)
Background and aims Over seven million women die from cardiovascular disease (CVD) annually. While lifestyle modification is recommended for CVD prevention, there are no systematic reviews evaluating the effectiveness of interventions targeted to women. The primary aim of this systematic review is to determine the efficacy of primary and secondary CVD prevention interventions targeting lifestyle risk factors in women. Methods Six electronic databases were searched up to January 2022. Eligible studies included randomized controlled trials of primary or secondary CVD prevention interventions targeting CVD lifestyle risk factors (diet, physical activity, sedentary behavior, smoking, alcohol, sleep, and weight management) in women (≥18 years) that reported CVD risk markers or lifestyle risk factors. Meta-analyses were conducted on CVD risk markers and body mass index (BMI), and the level of evidence was applied to the GRADE (Grading of Recommendations Assessment, Development and Evaluation) criteria and reported. Results Thirty-five RCTs were included (24 primary and 11 secondary prevention). Meta-analyses demonstrated that lifestyle CVD prevention interventions achieved statistically significant reductions in BMI at ≤ 6 months (0.95 kg/m2, 95% CI = 0.54 to 1.35, p < 0.0001), 12 months (0.61 kg/m2, 95% CI = 0.07 to 1.16, p = 0.03) and >12 months (0.58 kg/m2, 95% CI = 0.01 to 1.16, p = 0.05), and systolic blood pressure (mmHg) at ≤ 6 months (3.51, p < 0.001). Conclusions Lifestyle interventions are important for the prevention of CVD in women, specifically to reduce systolic blood pressure in the short term (≤ 6 months) and BMI long term (>12 months). Systematic review registration https://osf.io/bkwqm, identifier: osf-registrations-bkwqm-v1.